KEANEKARAGAMAN JENIS, KEPADATAN, DOMINANSI, DAN POLA PENYEBARAN ALGA MERAH DI PERAIRAN KALASEY MINAHASA SULAWESI UTARA - Try Falen D. Gampu; Deislie R. H. Kumampung; Veibe Warouw; Grevo S. Gerung; Chatrien A. L. Sinjal; Febry I. S. Menajang (JURNAL PESISIR DAN LAUT TROPIS, 2023)
The purpose of this study was to determine the species of red algae in Kalasey waters and also to determine their diversity, density, dominance, and distribution patterns. The research was conducted in November in the Kalasey Minahasa waters of North Sulawesi.This study used the quadrant transect method, in taking the sample the transect was drawn along 100m from the coastline towards the sea 3 times then the quadrants were placed on the side of the transect, each quadrant 10m apart was placed 10 times. From the use of this method, 5 species of red algae were obtained. Based on the results of data analysis, it showed that the diversity index was moderate with a value of 1.57 for the entire transect. The density index obtained from the results of data analysis with an overall transect value of 10.43. The distribution pattern index has a random distribution pattern with an overall transect value of 0.01. The overall dominance index of the transect is 1.21. The dominating species with the highest number of individuals was found in Gracilaria arcuata and the lowest number of individuals was found in Galaxaura fastigiata. The Kalasey waters area has a temperature of 33°C, a salinity of 30%o, and the degree of pH similarity obtained is 7. Based on the results of these parameters, the Kalasey waters are classified as good for the life of various types of algae.Keywords: Types of Red Algae, Kalasey WatersABSTRAKTujuan dari penelitian ini yaitu untuk mengetahui spesies alga merah yang ada di perairan Kalasey dan juga untuk mengetahui Keanekaragaman, Kepadatan, Dominansi, dan Pola Penyebarannya. Penelitian dilaksanakan pada bulan November di Perairan Kalasey Minahasa Sulawesi Utara. Penelitian ini menggunakan metode transek kuadran, pada pengambilan sampel transek ditarik sepanjang 100m dari garis pantai mengarah ke laut sebanyak 3 kali lalu kuadran diletakkan disisi Transek, setiap kuadran berjarak 10m diletakkan sebanyak 10 kali. Dari penggunaan metode tersebut diperoleh 5 spesies alga merah berdasarkan hasil dari analisis data menunjukkan bahwa indeks keanekaragaman sedang dengan nilai dari keseluruhan transek sebesar 1,57. Indeks kepadatan yang diperoleh dari hasil analisis data dengan nilai keseluruhan transek sebesar 10,43. Indeks pola penyebaran terdapat pola penyebaran acak dengan nilai keseluruhan transek sebesar 0,01. Indeks dominansi keseluruhan transek sebesar 1,21. Spesies yang mendominansi dengan jumlah individu tertinggi terdapat pada Gracilaria arcuata dan jumlah individu terendah terdapat pada Galaxaura fastigiata. Wilayah perairan Kalasey memiliki suhu 33°C, salinitas 30%o, dan derajat kesamaan pH yang diperoleh yaitu 7. Berdasarkan hasil parameter tersebut perairan Kalasey tergolong baik untuk kehidupan berbagai jenis alga.Kata kunci : Jenis Alga Merah, Perairan Kalasey